2004
DOI: 10.1002/j.1939-4640.2004.tb02859.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effects of Histone‐Deacetylase Inhibitor Trichostatin‐A on Murine Spermatogenesis

Abstract: ABSTRACT:The acetylation state of core histones is controlled by two classes of enzymes, histone acetyl transferases (HATs) and histone deacetylases (HDACs). HDAC inhibitors, such as trichostatin-A (TSA), are able to induce cell cycle arrest by stimulating transcription of genes that negatively regulate cell growth and survival. However, little is known about the effect of HDAC inhibitors on spermatogenesis. TSA treatment of cultured murine germ cells from whole testes resulted in an increase of histone H4 ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 29 publications
3
83
0
1
Order By: Relevance
“…Although testicular toxicities are common adverse side effects of cancer therapy (44), to our knowledge, investigators have not previously reported testicular pathology as a consequence of HDAC inhibitor treatment in preclinical models of human cancer. A single study examining the antifertility effect of trichostatin A in mice reported a completely reversible impairment of spermatogenesis resulting from increased apoptosis of spermatocytes (45). Although we do not know the cellular target mediating this toxicity of (S)-HDAC-42, the lack of pathologic changes in the pituitary and accessory sex organs suggests a primary testicular toxicity.…”
Section: Discussionmentioning
confidence: 88%
“…Although testicular toxicities are common adverse side effects of cancer therapy (44), to our knowledge, investigators have not previously reported testicular pathology as a consequence of HDAC inhibitor treatment in preclinical models of human cancer. A single study examining the antifertility effect of trichostatin A in mice reported a completely reversible impairment of spermatogenesis resulting from increased apoptosis of spermatocytes (45). Although we do not know the cellular target mediating this toxicity of (S)-HDAC-42, the lack of pathologic changes in the pituitary and accessory sex organs suggests a primary testicular toxicity.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, withdrawal of TSA led to complete regeneration of the seminiferous epithelium in fertility assays [74]. On the contrary, apoptosis of both spermatocytes and spermatids significantly increased with increasing TSA doses, suggesting for an inhibitory role of TSA mainly on meiosis but not mitosis [75,76]. During spermatogenesis, methylation of H3K and H4K histone tails is regulated by histone methyltransferases (HTM) and histone demethylases (HDM) [77,78].…”
Section: Role Of Histone Modifications In Male Infertilitymentioning
confidence: 99%
“…In mammals, reduced levels of histone H4 hyperacetylation correlates with impaired fertility (95,98).…”
Section: The Effects Of Bacterial Infection On Sperm Chromatin Condenmentioning
confidence: 99%